Forest Fire Resources and Services Case study: In Saida, Tyre and Bint-Jbiel Cazas - علي عبد الله سليمان (Latakia University Journal -Engineering Sciences Series, 2023)
INTRODUCTION: OVERVIEW : The forest fire problem has been a long-standing issue in Lebanon, posing a significant hazard and causing environmental damage. It is critical for the Lebanese environment to plan for control. Fire control services are important services in any community that strive to safeguard life and property. Objective of the project: General Objective : We propose to unleash a forest fire Resources Plan which put us all on the same track whenever a fire crisis occurs. Furthering from our resources and equipment also learning from our mistakes we are capable of making a change. Specific Objectives: To document how fire services are provided and the shortage in its resources in Saida, Tyre and Bint-Jbiel Cazas. Identify the water outlets in Saida, Tyre and Bint-Jbiel Cazas. To Identify fire frequencies that occurred in Saida, Tyre and Bint-Jbiel.